Technology in Catholic Schools: Are Schools Using the Technology They Have? - Gibbs, Michael G.; Dosen, Anthony J.; Guerrero, Rosalie B. (Catholic Education: A Journal of Inquiry and Practice, 2008)
This article examines important questions related to the use of computer technology in Catholic schools. Under consideration are issues related to how teachers use the Internet in classrooms, communicate with parents, and design lessons with technological support. Differences in computer use between high-poverty and low-poverty schools are also examined.